Dopamine Rebound-Excitation Theory: Putting Brakes on PTSD - Lee, Jason C.; Wang, Lei Philip; Tsien, Joe Z. (Frontiers in Psychiatry, 2016)
It is not uncommon for humans or animals to experience traumatic events in their lifetimes. However, the majority of individuals are resilient to long-term detrimental changes turning into anxiety and depression, such as post-traumatic stress disorder (PTSD). What underlying neural mechanism accounts for individual variability in stress resilience? Hyperactivity in fear circuits, such as the amygdalar system, is well-known to be the major pathophysiological basis for PTSD, much like a “stuck accelerator.” Interestingly, increasing evidence demonstrates that dopamine (DA) – traditionally known for its role in motivation, reward prediction, and addiction– is also crucial in regulating fear learning and anxiety. Yet how DA neurons control stress resilience is unclear, especially given that DA neurons have multiple subtypes with distinct temporal dynamics. Here, we propose the Rebound-Excitation Theory, which posits that DA neurons’ rebound-excitation at the termination of fearful experiences serves as an important “brake” by providing intrinsic safety-signals to fear-processing neural circuits in a spatially and temporally controlled manner. We discuss how DA neuron rebound-excitation may be regulated by genetics and experiences, and how such physiological properties may be used as a brain-activity biomarker to predict and confer individual resilience to stress and anxiety.